[Fe(nsal2trien)]SCN, a new two-step iron(III) spin crossover compound, with symmetry breaking spin-state transition and an intermediate ordered state - Vieira, Bruno J C; Coutinho, Joana T; Santos, Isabel C; Pereira, Laura C J; Waerenborgh, João C; da Gama, Vasco (Inorganic chemistry, 2013)
We report the synthesis of the iron(III) complex of the hexadentate Schiff base ligand nsal2trien obtained from the condensation of triethylenetetramine and 2 equiv. of 2-hydroxy-1-naphthaldehyde. The study of the salt [Fe(nsal2trien)]SCN (1) by magnetic susceptibility measurements and Mössbauer spectroscopy reveals a rather unique behavior that displays thermally induced spin crossover (SCO) with two well-separated steps at 250 (gradual transition) and 142 K (steep transition). Single crystal X-ray structures were obtained at 294, 150, and 50 K, for the high spin (HS), intermediate (Int), and low spin (LS) phases. The HS and LS phases are isostructural, and based on a single Fe(III) site (either HS or LS) an unusual symmetry break occurs in the transition to the Int ordered phase, where the unit cell includes two distinct Fe(III) sites and is based on a repetition of the [HS-LS] motif. The two-step SCO behavior of 1 must result from the existence of structural constraints preventing the full conversion HS ↔ LS in a single step.